Do isolated interstitial nickel atoms occur in diamond? A re-examination of the electron paramagnetic resonance defects NIRIM-1 and NIRIM-2 - Baker, M (2003)
All of the electron paramagnetic resonance (EPR) and optical data relating to some of the basic nickel-related defects in diamond have been compared, as well as previously little considered information about the effects of spin-orbit coupling and the magnitude of the crystal field. New models are proposed for the EPR defects, which are found in synthetic diamond grown at high pressure and high temperature with getters to reduce the content of nitrogen impurity: NIRIM-1 and NIRIM-2, which some authors have attributed to isolated interstitial nickel at an undistorted, or distorted, T-d site, respectively. It is suggested that NIRIM-1 is more likely to be substitutional Ni-s(+), 3d(5), at a T-d site, than the previously suggested interstitial Ni-i(+), 3d(9), and that NIRIM-2 is Ni-i(+), 3d(9), pinned at a site 0.308 nm along <111> from a B-s(-) impurity, beyond one of its nearest C neighbours. This supports the suggestion that isolated interstitial Ni-i is mobile.